2017
DOI: 10.1007/s13744-017-0527-x
|View full text |Cite
|
Sign up to set email alerts
|

Age Influence on Sexual Behavior of the Lesser Cornstalk Borer, Elasmopalpus lignosellus (Zeller) (Lepidoptera: Pyralidae)

Abstract: The objective of this work was to evaluate the reproductive behavior and response of Elasmopalpus lignosellus (Zeller) males to calling females. Frequency of mating was recorded in couples during the first 7 days of the adult stage. Calling behavior of females was observed during the first 4 days of the adult stage and responses of males, in the same age intervals, to calling females were recorded in wind tunnel bioassays. The maximum number of matings occurred when the couple was between 24 and 48 h old. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies also found that photoperiod and temperature affect the age that females initiate calling . This variation hints at physiological differences in sexual maturation, which could be an adaptation to changes in different photoperiodic and temperature conditions, especially for migratory species …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies also found that photoperiod and temperature affect the age that females initiate calling . This variation hints at physiological differences in sexual maturation, which could be an adaptation to changes in different photoperiodic and temperature conditions, especially for migratory species …”
Section: Discussionmentioning
confidence: 84%
“…Variation in timing of sexual behaviors in moths, such as female calling and pheromone release, has been extensively studied under laboratory conditions, showing that these sexual behaviors are affected by abiotic factors, such as photoperiod, temperature, relative humidity and wind speed . Sexual behaviors in moths may also be affected by biotic and physiological factors, such as age, host plants, larval diet, pupal period and insecticides . In addition, variation in moth sexual communication may be caused through communication interference between closely related species in areas of sympatry .…”
Section: Introductionmentioning
confidence: 99%
“…In moth species, geographic variation may arise as a result of avoiding inbreeding with closely related sympatric species that share key pheromone components (McElfresh and Millar, 1999;Groot et al, 2008;Sadek et al, 2012). Variation can also be manifested in the timing of sexual behaviours or be a consequence of physiological, biotic, and abiotic factors such as age (Swier et al, 1977;Noldus and Potting, 1990;Xavier et al, 2018), nutrition (Casimero et al, 2001), temperature (Conner et al, 1985;Delisle and McNeil, 1987), relative humidity (Webster and Carde, 1982;Royer and McNeil, 1991), photoperiod (Delisle and McNeil, 1986;Noldus and Potting, 1990;Kamimura and Tatsuki, 1994), host plants (Landolt and Phillips, 1997), wind speed (Conner et al, 1985), and insecticides (Shen et al, 2013;Navarro-Roldań and Gemeno, 2017). Therefore, it is essential to understand the local sex pheromone blends and local timings of sexual communication for effective field implementation of sex pheromone-dependent control tools (Gao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%